Clinical criteria for predicting the course of acute myocarditis in children (Texas Journal of Medical Science, 2026)
Acute myocarditis (OM) is an inflammatory disease caused by various infections, with viruses being the most widespread pathogenic factor [1, 2]. The pathophysiology of OM can be based on direct infection caused by a viral infection, inflammatory reactions after infection, or a combination of both.